Autophagy: a treatment option in neurodegenerative disease. (2nd June 2019) - Palmer, Sarah
Abstract : Sarah Palmer discusses a recent study that looked into the property of the drug felodipine in inducing cells to clear up toxic proteins. The study found that there is some scope to repurpose the drug as a treatment for neurodegenerative diseases.